1986
DOI: 10.1016/0014-5793(86)80191-0
|View full text |Cite
|
Sign up to set email alerts
|

Two phases of inositol polyphosphate and diacylglycerol production at fertilisation

Abstract: [3H]Inositol and [3H]arachidonic acid were used to label polyphosphoinositide phospholipids in sea urchin eggs. Both [3H]inositol polyphosphate (InsP3 and [3H]diacylglycerol (DAG) increase at fertilisation. An early increase in InsP, occurs as the sperm-induced calcium transient crosses the egg and exocytosis occurs; a later increase in InsP, as calcium declines and the protein kinase C-dependent Na/H antiporter causes the cytoplasmic pH to increase. These results support suggestions that a calcium-induced hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(60 citation statements)
references
References 24 publications
4
55
1
Order By: Relevance
“…It is very difficult to draw conclusions about the temporal sequence of cGMP and cADPR production, because, with the resolution available to us, both seem to peak at about the same time, roughly coincident with the peak of the population Ca 2ϩ transient. What we can say is that the timing of cADPR production at fertilization appears to be later than that of InsP 3 measured in a previous study (16) in L. pictus and suggests that cADPR regulates the later phase of the transient. Our data indicate cADPR levels peak at 200 nM at fertilization; cADPR levels of 40 -150 nM are reported to release Ca 2ϩ in intact sea urchin eggs on microinjection (5,10,11), so the increases we observe are physiologically relevant.…”
Section: Measurements Of Cadpr Levels At Fertilization Suggest Cadpr contrasting
confidence: 50%
See 2 more Smart Citations
“…It is very difficult to draw conclusions about the temporal sequence of cGMP and cADPR production, because, with the resolution available to us, both seem to peak at about the same time, roughly coincident with the peak of the population Ca 2ϩ transient. What we can say is that the timing of cADPR production at fertilization appears to be later than that of InsP 3 measured in a previous study (16) in L. pictus and suggests that cADPR regulates the later phase of the transient. Our data indicate cADPR levels peak at 200 nM at fertilization; cADPR levels of 40 -150 nM are reported to release Ca 2ϩ in intact sea urchin eggs on microinjection (5,10,11), so the increases we observe are physiologically relevant.…”
Section: Measurements Of Cadpr Levels At Fertilization Suggest Cadpr contrasting
confidence: 50%
“…cADPR levels have been previously shown to increase by 30 s after insemination in egg populations of the sea urchin species Anthocidaris crassispina and Hemicentrotus pulcherrimus (18). We have previously shown (16) that at appropriate sperm densities a peak of around 80% of eggs in a population are undergoing a Ca 2ϩ transient at 25 s after insemination. Fig.…”
Section: No Production At Fertilization Is Camentioning
confidence: 90%
See 1 more Smart Citation
“…Stricker's excellent survey of calcium signalling across the animal kingdom (Stricker 1999) demonstrates that all eggs from protostomes tested so far (cnidarians, nemerteans, molluscs and echiurans) respond to InsP 3 , as do algal gametes (Roberts & Brownlee 1995 (Nuccitelli et al 1993), sea urchins (Crossley et al 1991;Galione et al 1993;Lee et al 1993;Lee & Shen 1998;Mohri et al 1995), starfish (Stricker 1995;Santella et al 1999a), ascidians (McDougall & Sardet 1995 and mice (Kline & Kline 1994). Only in frog (Stith et al 1993(Stith et al , 1994 and sea urchin (Ciapa & Whitaker 1986;Kuroda et al 2001) eggs has InsP 3 been shown to increase at fertilization; measurements have not been reported in other species.…”
Section: Fertilization Second Messengersmentioning
confidence: 99%
“…Production and diffusion of InsP 3 can also participate in the reaction-diffusion mechanism underlying InsP 3 Rmediated calcium waves (Allbritton & Meyer 1993; Keizer et al 1995). Calcium may trigger further production of InsP 3 ( Whitaker & Aitchison 1985;Ciapa & Whitaker 1986;Ciapa et al 1992;Stith et al 1994). In support of this idea, a dominant negative PH domain inhibitor of PLCg not only delays the onset of the calcium wave, but also appears to diminish its propagation (Shearer et al 1999).…”
Section: Initiation and Propagation Of The Fertilization Calcium Wavementioning
confidence: 99%